Standardization of recipient surgery for uterus transplantation - Tamate, Masato; Johannesson, Liza; Bayer, Johanna; Testa, Giuliano (Fertility and sterility, 2025)
To present a standardized surgical technique of recipient transplant surgery for uterus transplantation (UTx). Step-by-step description of surgical technique and live-action narrated surgical footage showing uterus recipient surgery in UTx. Uterus transplantation can become a standard option for patients with absolute uterine factor infertility and their families (1, 2). Thirty-six uterus cases of UTx have been performed at Baylor University Medical Center in Dallas (January 2025). Most uterus recipients to date have a congenital absence of the uterus (Mayer-Rokitansky-Küster-Hauser syndrome [MRKH]). Our team has established standard methods for donor surgery and uterine graft back-table techniques. Because the uterus recipient surgery is typically performed using an open approach, high-quality educational videos of UTx are scarce. To aid institutions interested in initiating UTx, an educational video demonstrating our standardized recipient surgery is essential. This video shows the surgical procedure in a 39-year-old previously healthy woman with MRKH. The vascular nomenclature recommended by the United States Uterus Transplant Consortium is used in the manuscript (3). Uterus transplant recipient surgeries are performed via laparotomy and are significantly shorter than the living donor hysterectomies, averaging 4–5 hours (4). The operative steps performed are as follows: 1) exposure of the external iliac vessels; 2) exposure of the vaginal anastomosis site; 3) graft implantation and vascular anastomosis; 4) vaginal transection and anastomosis; and 5) fixation of the uterus and ovaries. Steps 1–2 are performed jointly by the gynecology surgeon and transplant surgeon; step 3, involving the anastomosis of blood vessels, is conducted by the transplant surgeon. Although steps 1, 2, 4, and 5 are not particularly challenging for an experienced gynecologic oncology surgeon, the vascular anastomosis in step 3 is delicate. This anastomosis involves suturing blood vessels smaller than those used in kidney and liver transplants, using 7-0 monofilament for the arterial and 8-0 monofilament for the venous anastomosis. After reperfusion of the uterine graft, the vaginal anastomosis is completed, which is where most of the bleeding occurs during surgery. For this step (step 4), we use continuous suturing from the 3 to 9 o'clock positions. The vaginal approach is preferred because of the challenging anatomy, particularly in patients with MRKH, where the foreshortened vagina lies deep in the pelvis. Continuous sutures are used for hemostasis in the posterior vaginal wall, where venous blood flow is abundant. To attempt prevention of vaginal structuring, the anterior vaginal wall is sutured interrupted. Step 5 includes fixation of the uterus and ovaries. A trained gynecology surgeon is essential, because the technique may vary depending on the condition of the patient with MRKH. Before implantation of the uterine graft in the recipient, the uterus is removed from a living or deceased donor and subsequently placed on ice and flushed with cool preservation fluid on the back table. The back table is a sterile area used in transplantation surgery where the organ is prepared for transplantation. Preparation includes trimming and potential 86 reconstructions of the vessels that will be used. The living donor hysterectomy and the back table procedure can be seen in separate videos. Hospital stay, perioperative, and long-term complications. Uterine graft viability and recipient pregnancy outcome. No surgical complications occurred. The postoperative course was uneventful, with early mobilization. The length of hospital stay was 5 days. The uterus was successfully implanted with a successful pregnancy outcome. Our standardized uterus recipient surgery technique minimizes harm to the recipient. Furthermore, the technique does not compromise the uterine graft function and pregnancy outcome. Further studies and more educational content using video will be key to the widespread adoption of uterine transplantation. Estandarización de la cirugía de receptoras para trasplante de útero. Presentar una técnica quirúrgica estandarizada para la cirugía de receptoras de útero (UTx). Descripción paso a paso de la técnica quirúrgica e imágenes quirúrgicas narradas en vivo que muestran la cirugía de receptoras de útero en UTx. El trasplante de útero puede convertirse en una opción estándar para pacientes con infertilidad absoluta por factor uterino y sus familias (1, 2). Se han realizado treinta y seis casos de UTx en el Centro Médico de la Universidad de Baylor en Dallas (enero de 2025). Hasta la fecha, la mayoría de las receptoras de útero presentan una ausencia congénita del útero (síndrome de Mayer-Rokitansky-Käuser-Hauser [MRKH]). Nuestro equipo ha establecido métodos estandarizados para la cirugía de donante y las técnicas de injerto uterino en mesa posterior. Dado que la cirugía de la receptora de útero se realiza típicamente mediante un abordaje abierto, escasean los videos educativos de alta calidad sobre UTx. Para ayudar a las instituciones interesadas en iniciar UTx, es esencial un video educativo que demuestre nuestra cirugía estandarizada para la receptora. Este video muestra el procedimiento quirúrgico en una mujer de 39 años previamente sana con MRKH. En el manuscrito se utiliza la nomenclatura vascular recomendada por el Consorcio de Trasplante de Útero de los Estados Unidos (3). Las cirugías de las receptoras de trasplante de útero se realizan mediante laparotomía y son significativamente más cortas que las histerectomías de donante viva, con una duración promedio de 4 a 5 horas (4). Los pasos quirúrgicos son los siguientes:c1) exposición de los vasos ilíacos externos; 2) exposición del sitio de anastomosis vaginal; 3) implantación del injerto y anastomosis vascular; 4) transección vaginal y anastomosis; y 5) fijación del útero y los ovarios. Los pasos 1 y 2 son realizados conjuntamente por el cirujano ginecólogo y el cirujano de trasplantes; el paso 3, que implica la anastomosis de los vasos sanguíneos, es realizado por el cirujano de trasplantes. Si bien los pasos 1, 2, 4 y 5 no son particularmente desafiantes para un cirujano ginecológico oncológico experimentado, la anastomosis vascular del paso 3 es delicada. Esta anastomosis implica la sutura de vasos sanguíneos más pequeños que los utilizados en trasplantes de riñón e hígado, utilizando laminado monofilamento 7-0 para la anastomosis arterial y monofilamento 8-0 para la venosa. Tras la reperfusión del injerto uterino, se completa la anastomosis vaginal, que es donde se produce la mayor parte del sangrado durante la cirugía. Para este paso (paso 4), utilizamos sutura continua desde las posiciones de las 3 a las 9 en punto. Se prefiere el abordaje vaginal debido a la anatomía compleja, especialmente en pacientes con MRKH, donde la vagina, en escorzo, se encuentra profundamente en la pelvis. Se utilizan suturas continuas para la hemostasia en la pared vaginal posterior, donde el flujo sanguíneo venoso es abundante. Para intentar prevenir la estructuración vaginal, se sutura la pared vaginal anterior con puntos interrumpidos. El paso 5 incluye la fijación del útero y los ovarios. Es esencial contar con un cirujano ginecólogo capacitado, ya que la técnica puede variar según la condición de la paciente con MRKH. Antes de la implantación del injerto uterino en la receptora, se extrae el útero de una donante viva o fallecida y posteriormente se coloca en hielo y se lava con líquido de conservación frío en la mesa de operaciones. La mesa de operaciones es un área estéril utilizada en la cirugía de trasplante donde se prepara el órgano para el trasplante. La preparación incluye el recorte y las posibles reconstrucciones de los vasos que se utilizarán. La histerectomía de donante viva y el procedimiento en mesa de operaciones se pueden ver en videos separados. Estancia hospitalaria, complicaciones perioperatorias y a largo plazo. Viabilidad del injerto uterino y resultado del embarazo de la receptora. No se presentaron complicaciones quirúrgicas. El postoperatorio transcurrió sin incidentes, con movilización temprana. La estancia hospitalaria fue de 5 días. El útero se implantó con éxito, con un resultado positivo del embarazo. Nuestra técnica estandarizada de cirugía de receptora de útero minimiza el daño a la receptora. Además, la técnica no compromete la función del injerto uterino ni el resultado del embarazo. Estudios adicionales y más contenido educativo mediante videos serán clave para la adopción generalizada del trasplante uterino.